Interplay of autophagy and Th1/Th2-mediated macrophage polarization in host-pathogen dynamics - Shoeran, Gaurav; Anand, Namrata (Frontiers in Cellular and Infection Microbiology, 2025)
Autophagy, host immune responses, and macrophage polarization form a tightly regulated network. This network significantly influences the outcome of intracellular pathogenic infections. Autophagy acts as a critical cellular defense mechanism. It degrades intracellular pathogens and helps with antigen presentation in antigen presenting cells like macrophages. Intracellular parasites have evolved diverse strategies to modulate autophagy. They may inhibit autophagosome formation, block autophagosome-lysosome fusion, or redirect autophagic flux for their survival. These manipulations allow pathogens to evade degradation and persist within host cells. Macrophage polarization further influences autophagic activity: M1 macrophages typically exhibit enhanced autophagy, supporting antimicrobial functions, while M2 macrophages show reduced autophagic flux, contributing to immune regulation and tissue repair. Autophagy itself can influence macrophage phenotypes, with its activation promoting M1-like characteristics and its inhibition favoring M2-like responses. The macrophage polarization states influence T cell polarization and infection outcome. This bidirectional relationship between autophagy and macrophage polarization plays a pivotal role in determining host resistance or susceptibility to intracellular pathogens. In this review, we highlight findings from macrophage-infecting pathogens that manipulate autophagy, macrophage and T cell to enhance their survival within the host.